Modelagem da estrutura trófica da comunidade biótica de uma bacia costeira em Bertioga – SP - Silva, Victoria Pinheiro Gonçalves da (2022)
Environmental characteristics and trophic relationships in streams of the Atlantic Forest can interfere the ichthyofauna’s food webs which, in addition to a seasonal oscillation in the water cycle, can affect the structuring of the community. The objective of the work was to verify the influence of structural and limnological variables, ecosystem development patterns and the water cycle on food webs in 11 coastal streams in a one-year period in Bertioga (SP). The samplings took place monthly between may 2016 and april 2017, with an electric fishing device. A taxonomic sorting and biometry were performed with the captured specimens for a later dissection and fixation of the stomachs. A mathematical model was created for each stream in Ecopath with Ecosim. The annual analyzes consisted of a Principal Component Analysis (PCA) with environmental data to verify structural and limnological differences between streams, then a grouping with presence/absence of species to observe distribution patterns, and a Redundancy Analysis (RDA) with environmental data and ecosystem parameters to identify the influence of variables on food webs. The seasonal analyzes consisted of a PCA to observe the occurrence of seasonality on the environmental data, then a t-test was applied to verify statistical differences between the wet and dry periods with the measured attributes, where these attributes were later plotted in a PCA to observe seasonality between streams, and a Key Species Index to identify the central species of the food webs. Environmental characteristics, such as width, depth, flow, substrate, dissolved oxygen and pH, differentiated between the clear and blackwater streams, and in the distribution pattern of the ichthyofauna as well. The ecosystem attributes influenced the trophic webs of the streams, and the studied environments are stable with a certain degree of resilience, however, still in the process of ecosystem development. The absence of seasonal variation in environmental data and some of the ecosystem attributes is due to the constant rainfall in the region and the presence of dense riparian forest around the channels, which may have favored an increase in the availability of food items, contributing to the shortening of the trophic chains. Top-down and wasp-waist effects were observed in ecosystems in the region, varying between streams and, in some cases, seasonally as well.